Strengthening Student Sexual Literacy to Prevent Violence in Indonesian Islamic Boarding Schools - Chanifah, Nur; Ikhsan, M. Alifuddin; Syaikhoni; Luth, Thohir (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
This study examines sexuality literacy among students of Indonesian Islamic boarding schools (pesantren) as institutions historically central to moral and character development, yet recently marred by cases of sexual violence. Such incidents urgently require preventive reforms and decisive action against perpetrators. The research describes students’ knowledge, attitudes, and practices regarding sexuality literacy, their textual and contextual interpretations of Qur’anic verses, and school policies for preventing sexual violence. Using surveys, focus groups, and interviews, the study explores students’ perspectives and lived experiences in a pluralistic society. Findings reveal that strengthening sexuality literacy rooted in the Qur’an is achieved through four strategies. There are direct studies using a Sexuality Literacy Module and thematic Qur’anic interpretation, integration into fiqh studies, incorporation into moral education, and cultivation of a gender-sensitive, safe school culture. This research offers a practical framework for pesantren to align sexual education with Islamic teachings while addressing contemporary challenges. By demonstrating how critical-reflective Qur’anic learning fosters informed, gender-aware students, it provides policy guidance for educators, religious leaders, and regulators seeking to reduce sexual violence and promote holistic character formation in Islamic educational institutions.